Design and analysis of structured controllers - Antonius Yudi Sendjaja (2011)
For control of industrial processes, although fully centralized high-order controllers can theoretically provide good performance, simple controllers are used in practice due to the ease in design, maintenance, and operator acceptability. These simple controllers often have a structure, e.g. only certain elements of controller are allowed to be non-zero or the controller is restricted to be a low order transfer function. In this thesis, several tools are developed for design, analysis and assessment of such structured controllers, namely RTD-A, PID, and decentralized controllers.